CAVITATION-EROSION STUDY IN ELBOW TUBES OF A LOW-PRESSURE EVAPORATOR OUTLET HEADER - Dewa Nyoman Adnyana (Metalurgi, 2020)
This paper presents the results of the cavitation-erosion study that occurred on elbow tubes that connected to the low-pressure (LP) Evaporator outlet header on a heat-recovery steam generator (HRSG) unit. Inside the elbow tubes flow the working fluid in the form of hot water with a pressure of 10 bar and a temperature of 160° C. Elbow tubes are made of low carbon steel, have an outer diameter of 31.8 mm and a wall thickness of 2.6 mm. Before entering into the elbow tubes, the working fluid warms up inside the evaporator tubes panel using hot flue gases coming from a gas turbine power plant unit. In this study there were 4 (four) pieces of post-service elbow tubes used, namely elbow tube with the connecting angle of 90°, 75°, 60° and 45°. The types of tests carried out included macroscopic tests, chemical analysis, metallographic examinations, hardness tests and EDS (energy dispersive spectroscopy) analysis. The study results obtained show that the elbow tubes undergo a process of thinning on the inner wall of the outer curvature with a rough and jagged surface appearance. This type of failure is known cavitation- erosion. The level of cavitation-erosion that occurs is very much influenced by the elbow’s connecting angle with the LP Evaporator header outlet. The greater the connecting angle or the smaller the radius of the elbow tube, the higher the level of cavitation-erosion that occurs. The high rate of cavitation-erosion experienced by the four elbow tubes is also related to the level of turbulence of the working fluid flow that occurs in the elbow tube. The increase in turbulence that occurs is caused by a decrease in the pressure of the working fluid in the evaporator panel so that some part of the working fluid turns into steam and produces a two-phase flow consisting of a mixture of water and steam